Media Sosial dan Aplikasi Kecerdasan Buatan Dalam Preferensi dan Partisipasi Pemilih Di Pemilihan Umum - Nunik Hariyani; Alfiana Yuniar Rahmawati (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
The advancement of internet-based information technology has made online social networks essential for general elections. Social media plays a positive role by increasing voter participation in politics. This study aims to analyze voter preferences regarding the use of social media during elections and to examine how artificial intelligence applications can be employed to engage voters. The research involves conducting surveys and performing system analyses. The results indicate that social media influences 59.3% of voters, establishing it as the primary platform for political information and communication. Artificial intelligence-based applications are designed to attract young voters through innovative interactions and personalized experiences. These applications can serve as effective modern campaign tools to reach a broader audience of voters